The impact of Split-Share Structure Reform on earnings quality: Evidence from China - ZHANG, KUNWEI (2016)
This study examines the effect Split-share Structure Reform on earnings quality in Chinese listed firms. In 2005, Chinese Securities Regulatory Commission (CSRS) conducted the Split-share Structure Reform converted non-tradable shares to tradable shares. This reform was discussed to constrained earnings management in Chinese listed firms and reduced information asymmetry. This paper investigates the whether this event has any influence on earnings manipulation in China. Also, considering mandatory adoption of IFRS in China from 2007, this study separates the A-shares and B-shares to measure earnings management, which increased comparability of earnings quality between A-shares and B-shares, as well as eliminates the effects of IFRS. In addition, this paper examines the association between non-tradable shares and earnings management, as well as the effect of increasing in tradable shares on earnings quality.